Wiggsy Sivertsen and Ken Yeager at an event - Sahl, Ted (photographer):::Creator::::::::::::
Wiggsy Sivertson and Ken Yeager stand between several banquet tables of people at an unidentified event. Elizabeth Birch is seated in the chair in front of Yeager. Arthur Morris is seated at the far right front partially facing the camera. There are balloons with stars on them as centerpieces at each table.